Analisis Soal pada Buku Matematika Kelas VIII Kurikulum 2013 (Buku Siswa) Ditinjau dari Aspek Kognitif TIMSS - Cahyanti, Novi Dwi, Prof. Dr. Budi Murtiyasa, M.Kom (2017)
This study aims to analyze and describbe the mathematics problems in the eight grade mathematics textbook K-13 based cognitif domain Trends International Mathematics and Science Study (TIMSS) 2015 frameworks. The basis of this study is the low ability students at TIMSS survey. The fact mathematics problems in the textbook hasn't challenged the students to think logically, creative, and critically. The object of this study was the revised editionn of 1st and 2nd semester textbook of eight grade mathematics published by Ministry of Education an Culture in 2014. Questions analyzed include practice at the end section , competency test at the end of the chapter, and half of the competency test. Questions is classified in to cognitif domain include knowing, applying, and reasoning, then classified on each indicators cognitif domain. This study is using content analysis method. Data were collected through document analysis and interview. The result of this study indicated percentage of knowing is 24,31%, applying is 46,54%, and reasoning is 29,15%. It shows at the textbook has provided reasoning to familiarize students of problem solving need reasoning, soit is xpected to contribute the achievement Indonesia's educations.